Early stage ovarian cancer: the Italian contribution to clinical research. An update. (1st July 2001) - Favalli, G.; Odicino, F.; TORRI, V.; Pecorelli, S.
Abstract : Favalli G, Odocino F, Torri V, Pecorelli S. Early stage ovarian cancer: the Italian contribution to clinical research. An update. Early ovarian cancer (stages IA–IIA) accounts for 30% of all epithelial ovarian cancer. Even if relatively uncommon, when "high risk" patients are considered, it is lethal in 25–30% of the cases. Mainstay of treatment is surgery followed by either adjuvant chemotherapy or radiotherapy when indicated on the basis of still debatable prognostic factors. Literature data show a great variability in survival rate due to the great heterogeneity of patients considered in different reports and few randomized trials affected by a consequent low power. Italian groups have contributed both in investigating the role of surgery and of chemo or radiotherapy in the treatment of this disease. An important contribution in surgery has been made by Italian institutions in reducing the extent of surgery in young patients wishing to retain their reproductive capability showing that a "conservative surgery" (unilateral oophorectomy) can be safely performed in initial stages without affecting the probability of cure. Another important surgical topic investigated by Italian institutions concerns the role of lymphadenectomy. In early ovarian cancer the node involvement ranges between 14–24% in stage I and 37–50% in stage II. Although the node positivity rate detectable by sampling (SA) is lower than the one shown by a systematic procedure (LY), no data at the moment show that patients undergoing a sampling evaluation have a poorer prognosis. From 1992 through 1994, 202 patients (SA: 99; LY: 103) were enrolled by six Italian institutions in a randomized trial aimed to assess the diagnostic and therapeutic role of SA vs. LY in early stage ovarian cancer. Positive nodes were detected in 9.9% vs. 19.3% respectively as well as a different proportion of intra/perioperative complications occurred. No difference in time to relapse nor in overall survival were detected in the two groups showing no evidence of efficacy in favor of extensive staging of the retroperitoneum. From 1983 to 1990, 271 stage I ovarian cancer patients entered two prospective multicentric randomized trials conducted by Italian institutions. Trial I compared cisplatin (50 mg/m 2, six cycles repeated every 28 days) vs. no further treatment in stage IA–B grade 2–3 patients; Trial II compared the same dose and schedule of cisplatin vs. intraperitoneal P32 in stage IC patients. Cisplatin significantly reduced the relapse rate by 65% in Trial I and by 61% in Trial II, but survival was not affected (Trial I: HR = 1.15, 95% CI = 0.44–2.98; Trial II: HR = 0.72, 95% CI = 0.37–1.43). The final conclusion drawn by these two important Italian studies was that adjuvant cisplatin treatment in early ovarian cancer prevents relapse although the impact of chemotherapy remains unclear. For this reason two international trials have been performed (ICON1 and ACTION) aimed at assessing the role of platinum-based chemotherapy on survival. Italian collaboration in both trials has been important, including about half of the total number of the 900 randomized patients. Results will probably be available during this year and are expected with a great interest by the whole scientific international community.